Evaluation of the Pharmacological Properties of Piscine Venoms from both Lionfish (Pterois) and Stonefish (Synanceja) - Ramalingam, Karthikeyan (Current Enzyme Inhibition, 2021)
Background: For the past 70 years, the focus of research is on the search for poisons and toxins found in venomous and poisonous organisms, purely directed towards the pharmacological properties of the toxins. In the research of finding novel compounds in pharmaceutical research, the identified source was the piscine venom. Objective: The Scorpaenidae family was considered the most venomous of all. The toxins isolated from stonefish and lionfish are responsible for the effects caused in cardiovascular and neuromuscular systems and also for causing cytolytic activities. The main objective of the review is to study the mechanism of the stonefish venom and portray its benefits in the field of drug discovery. Methods: A study on the mechanism of stonefish venom was carried out by inducing cardiovascular endothelium. The release of neurotransmitter signals thus leads to the depolarisation of cell membrane by the formation of pores in the cell membrane in the neuromuscular system of rabbits, porcine artery, mice and rats. Lionfish venom in cross-reactivity with the results evolved from a stonefish venom activity. The presence of enzymatic hyaluronidases in the primary structures of lionfish has evolved from stonefish and their anticancer potential has also been demonstrated for the benefits of drug discovery as they possess biological and chemical activity. Conclusion: This review depicts an overview of the pharmacological activities of lionfish venom in comparison with the stonefish venom and their purpose of applications for future research in drug discovery.
Keywords: Lionfish venom